Oxygen Reduction, Transport and Separation in Low Silver Content Scandia-Stabilized Zirconia Composites - Ruiz-Trejo,E; Bertei,A; Maserati,A; Boldrin,P; Brandon,NP (Journal of The Electrochemical Society, 2017)
Dense composites of silver and Sc-stabilized ZrO2 (Ag-ScSZ) are manufactured from ScSZ sub-micrometric particles coated with silver using Tollens’ reagent. A composite with 8.6 vol % of silver exhibits metallic conductivity of 186 S cm−1 and oxygen flux of 0.014 μmol cm−2 s−1 at 600°C for a 1-mm thick membrane when used as a pressure-driven separation membrane between air and argon. To gain insight into the role of oxygen transport in Ag and ScSZ, a dense non-percolating sample (Ag 4.7 vol%) is analyzed by impedance spectroscopy and the transport of oxygen through both phases is modelled. Oxygen transport takes place in both silver and ScSZ but it is still dominated by transport in the ionic conductor and therefore a large volume fraction of the ion conductor is beneficial for the separation. The oxygen transport in the silver clusters inside the composite is dominated by diffusion of neutral species and not by the charge transfer reaction at the interface between ScSZ and Ag, yet small silver particles on the surface improve the reduction of oxygen. Oxygen reduction is highly promoted by silver on the surface and there are no limitations of charge transfer at the interface between silver and ScSZ.